Neurofibromatosis associated with retinoblastoma: case report. Issue 2 (February 1988) - Hasanreisoğlu, B.; Or, M.; Akbatur, H.
Abstract : A case of neurofibromatosis is presented in a 3-year-old male with leucokoria in his left eye. Enucleation was performed, and on pathological examination the mass filling the globe proved to be retinoblastoma. We believe ours to be the first reported case of this rare association.